Ethics of Dialogue and Relating with Others from the Qur’anic Perspective: An Analytical Study of Modern Exegesis - ishak, Mohd. Shuhaimi; Solihin, Sohirin Mohammad
This research studies the ethics of dialogue and relating with others as embodied in the Qur`an based on exegesis written by contemporary exegetes. It concentrates on verses which highlight the most appropripate manner to deal with others. The ethics of dialogue and relation comprises the whole aspect of sociological context which could be actualized in the form of concept of knowledge for human benefits. In view of lack of proficiency in Arabic, the most appropriate and convinient way of understanding the Qur’an is to look into the views of contemporary exegetes. Ethical guidelines in the Qur`an surveyed in this study may help the readers to be sensitized on handling relationship problems, religious and communal tension which have plagued our world today.